Regulations for the electrical and electronic equipment of ships with recommended practice for their implementation (Institution of electrical engineers, 1990)
These updated Regulations and Recommended Practice apply to the electrical equipment for the generation, storage, conversion, distribution and utilization of electrical energy for all except war ships and include, where relevant, inland and harbor craft. They are intended to provide satisfactory operation and safety, especially from fire and shock, of installed equipment and portable and transportable equipment which is intended to be connected to the ships's distribution system.